2017
DOI: 10.3892/mco.2017.1522
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of osimertinib in a patient with non‑small cell lung cancer harboring epithelial growth factor receptor exon 19 deletion/T790M mutation, with poor performance status

Abstract: Osimertinib, a third-generation epithelial growth factor receptor (EGFR) tyrosine kinase inhibitor, has been demonstrated to be effective for treating patients with T790M-positive advanced non-small cell lung cancer (NSCLC) with a relatively good performance status (grade 0–1). Reports of therapeutic response to osimertinib in advanced NSCLC patients with poor performance status are infrequent. The present case report discusses a patient with advanced lung adenocarcinoma harboring EGFR exon 19 deletion and T79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Several researches have clarified that NSCLC patients harboring EGFR exon 19 deletion or exon 21 L858R can benefit from icotinib and osimertinib. 26,27 In this study, 38.82% of MM patients bearing EGFR mutations in the 18-21 exon region, among which exon 19 deletion and L858R accounted for 62.5% of all EGFR mutations. The lung adenocarcinoma patients harboring sensitive EGFR mutations benefit from EGFR-TKI drugs.…”
Section: Discussionmentioning
confidence: 58%
“…Several researches have clarified that NSCLC patients harboring EGFR exon 19 deletion or exon 21 L858R can benefit from icotinib and osimertinib. 26,27 In this study, 38.82% of MM patients bearing EGFR mutations in the 18-21 exon region, among which exon 19 deletion and L858R accounted for 62.5% of all EGFR mutations. The lung adenocarcinoma patients harboring sensitive EGFR mutations benefit from EGFR-TKI drugs.…”
Section: Discussionmentioning
confidence: 58%
“…Takashi et al [ 9 ] demonstrated that osimertinib regressed bone tumors in mice with EGFR-mutant lung adenocarcinoma and bone metastases, resulting in improved survival and bone remodeling in the mice. Similarly, Ying et al [ 10 ] and Yoichi et al [ 11 ] reported that patients treated with osimertinib experienced regression of bone metastases and longer-term survival rates. These findings align with those of our study, in which patients with bone metastases from lung adenocarcinoma with EGFR 19del mutation had longer-term control of both primary tumors and bone metastases, with PFS of 18 and 22 months and even longer OS after targeted therapy with osimertinib, following different treatments such as chemotherapy, radiotherapy, and surgery.…”
Section: Discussionmentioning
confidence: 97%
“…This suggests that patients with advanced EGFR m+ NSCLC despite having poor ECOG performance status, do derive OS benefits when treated with EGFR TKIs as previously reported. 27 , 28 …”
Section: Discussionmentioning
confidence: 99%